From climate change to analytical advances on mycotoxin research: key insights from the 46th Mycotoxin Workshop - Antonio Moretti; Martina Loi; Vincenzo Lippolis; Annalisa De Girolamo; Francesca Fanelli; Benedikt Cramer (Mycotoxin Research, 2026)

Disruption of serotonin homeostasis in intestinal organoids provides insights into drug-induced gastrointestinal toxicity - Georgia M. Rouseti; Audrey Fischer; Nicole Rathfelder; Karen Grimes; Annick Waldt; Rachel Cuttat; Sven Schuierer; Sophia Wild; Magali Jivkov; Valerie Dubost; Heiko S. Schadt; Alex Odermatt; et al. (Toxicology, 2025)

Belimumab 10 years later: how drug positioning has changed - Fulvia Ceccarelli; Francesco Natalucci; Claudia Ciancarella; Licia Picciariello; Valeria Moretti; Francesca Romana Spinelli; Cristiano Alessandri; Fabrizio Conti (Immunologic Research, 2024)
We analysed the change in the positioning of belimumab (BLM) in systemic lupus erythematosus (SLE) treatment in the first decade of real-life use, by providing data about patients treated by this biological drug in the Sapienza Lupus Cohort. We evaluated SLE patients treated by BLM according to the current clinical practice. Data of each patient were collected, focusing on previous and concomitant treatments. Finally, the drug retention rate was assessed. Since August 2013, 138 SLE patients started BLM (M/F 7/131; median age 49 years, IQR 13.25; median disease duration 214 months, IQR 180). To evaluate the change in BLM positioning, we divided patients according to the date of starting treatment as below: patients treated from 2013 to 2018 (period 1) and those treated since 2019 to date (period 2). Indeed, the median number of previous immunosuppressant drugs was significantly higher in patients treated in period 1 [3 (IQR 1.25) versus 1 (IQR 1.75), p = 0.0002]. Furthermore, 15.9% of patients treated in period 2 were not previously treated by immunosuppressant drugs, compared with 5.2% in period 1 ( p = 0.01). Finally, the 24-month drug survival was significantly higher in patients previously treated with ≤ 1 immunosuppressant drug in comparison with those treated with ≥ 2 drugs (69.1% versus 43.4%, p = 0.0097, HR 0.49; 95% CI 0.27–0.88). Our data clearly described the progressive anticipation of BLM prescription in the first 10 years of clinical practice, underlining as choosing earlier biological agents could positively influence the drug retention rate.

The environmental and agronomic benefits and trade-offs linked with the adoption alternate wetting and drying in temperate rice paddies - Andrea Vitali; Barbara Moretti; Chiara Bertora; Eleonora Francesca Miniotti; Daniele Tenni; Marco Romani; Arianna Facchi; Maria Martin; Silvia Fogliatto; Francesco Vidotto; Luisella Celi; Daniel Said-Pullicino (Field Crops Research, 2024)

EU2030 biodiversity strategy: Unveiling gaps in the coverage of ecoregions and threatened species within the strictly protected areas of Italy - Roberto Cazzolla Gatti; Jacopo Iaria; Gloria Moretti; Valerio Amendola; Francesca Maura Cassola; Pierfilippo Cerretti; Michele Di Musciano; Luana Francesconi; Anna Rita Frattaroli; Martina Livornese; Matilde Martini; Dario Nania; et al. (Journal for Nature Conservation, 2024)

Agro-ecosystem of honeybees as source for native probiotic yeasts - Alice Agarbati; Laura Moretti; Laura Canonico; Maurizio Ciani; Francesca Comitini (World Journal of Microbiology and Biotechnology, 2024)
Probiotic microorganisms are used to improve the health and wellness of people and the research on this topic is of current relevance and interest. Fifty-five yeasts, coming from honeybee’s ecosystem and belonging to Candida , Debaryomyces , Hanseniaspora , Lachancea , Metschnikowia , Meyerozyma , Starmerella and Zygosacchromyces genera and related different species, were evaluated for the probiotic traits. The resistance to gastrointestinal conditions, auto-aggregation, cell surface hydrophobicity or biofilm formation abilities as well as antimicrobial activity against common human pathogenic bacteria were evaluated. The safety analysis of strains was also carried out to exclude any possible negative effect on the consumer’s health. The influence of proteinase treatment of living yeasts and their adhesion to Caco-2 cells were also evaluated. The greatest selection occurred in the first step of survival at the acidic pH and in the presence of bile salts, where more than 50% of the strains were unable to survive. Equally discriminating was the protease test which allowed the survival of only 27 strains belonging to the species Hanseniaspora guilliermondii , Hanseniaspora uvarum , Metschnikowia pulcherrima , Metschnikowia ziziphicola , Meyerozyma caribbica , Meyerozyma guilliermondii , Pichia kluyveri , Pichia kudriavzevii and Pichia terricola . An integrated analysis of the results obtained allowed the detection of seven yeast strains with probiotic aptitudes, all belonging to the Meyerozyma genus, of which three belonging to M. guillermondii and four belonging to M . caribbica species.

First evidence of widespread positivity to anticoagulant rodenticides in grey wolves (Canis lupus) - Carmela Musto; Jacopo Cerri; Dario Capizzi; Maria Cristina Fontana; Silva Rubini; Giuseppe Merialdi; Duccio Berzi; Francesca Ciuti; Annalisa Santi; Arianna Rossi; Filippo Barsi; Luca Gelmini; et al. (Science of The Total Environment, 2024)

Genotoxicity assessment of 1,4-anhydro-4-seleno-D-talitol (SeTal) in human liver HepG2 and HepaRG cells - Raffaella di Vito; Mattia Acito; Cristina Fatigoni; Carl H. Schiesser; Michael J. Davies; Francesca Mangiavacchi; Milena Villarini; Claudio Santi; Massimo Moretti (Toxicology, 2023)

Analytical study on the primary and secondary organic carbon and elemental carbon in the particulate matter at the high-altitude Monte Curcio GAW station, Italy - Sacha Moretti; Antonella Tassone; Virginia Andreoli; Francesco Carbone; Nicola Pirrone; Francesca Sprovieri; Attilio Naccarato (Environmental Science and Pollution Research, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Occurrence of deoxynivalenol in an elderly cohort in the UK: a biomonitoring approach - Maria Papageorgiou; Liz Wells; Courtney Williams; Kay L.M. White; Barbara De Santis; Yunru Liu; Francesca Debegnach; Brunella Miano; Giorgio Moretti; Stephanie Greetham; Carlo Brera; Stephen L. Atkin; et al. (Food Additives & Contaminants: Part A, 2018)

Micronuclei and chromosome aberrations in subjects occupationally exposed to antineoplastic drugs: a multicentric approach - Massimo Moretti; Maria Giuseppa Grollino; Sofia Pavanello; Roberta Bonfiglioli; Milena Villarini; Massimo Appolloni; Mariella Carrieri; Laura Sabatini; Luca Dominici; Laura Stronati; Giuseppe Mastrangelo; Anna Barbieri; et al. (International Archives of Occupational and Environmental Health, 2015)

Two GUIs-based analysis tool for spectroradiometer data pre-processing - Francesca Garfagnoli; Gianluca Martelloni; Andrea Ciampalini; Luca Innocenti; Sandro Moretti (Earth Science Informatics, 2013)

Remote sensing techniques using Landsat ETM+ applied to the detection of iron ore deposits in Western Africa - Andrea Ciampalini; Francesca Garfagnoli; Benedetta Antonielli; Sandro Moretti; Gaia Righini (Arabian Journal of Geosciences, 2013)

Potential Use of Remote Sensing Techniques for Exploration of Iron Deposits in Western Sahara and Southwest of Algeria - Andrea Ciampalini; Francesca Garfagnoli; Chiara Del Ventisette; Sandro Moretti (Natural Resources Research, 2013)

Forest humus forms as potential indicators of soil carbon storage in Mediterranean environments - Anna Andreetta; Rossano Ciampalini; Pierpaolo Moretti; Simona Vingiani; Giorgio Poggio; Giorgio Matteucci; Francesca Tescari; Stefano Carnicelli (Biology and Fertility of Soils, 2011)

Analysis of human MDM4 variants in papillary thyroid carcinomas reveals new potential markers of cancer properties - Andrea Prodosmo; Simona Giglio; Sonia Moretti; Francesca Mancini; Flavia Barbi; Nicola Avenia; Giusy Di Conza; Holger J. Schünemann; Lorenza Pistola; Vienna Ludovini; Ada Sacchi; Alfredo Pontecorvi; et al. (Journal of Molecular Medicine, 2008)

First report of oral colonization by Debaryomyces nepalensis in a dog - Annabella Moretti; Kazutaka Fukushima; Kayoko Takizawa; Motofuni Suzuki; Valerio Vidotto; Francesca T. Cannizzo; Luisa Boncio; Enrico Bollo (Mycopathologia, 2007)

Stem cell factor affects tumour progression markers in metastatic melanoma cells - Francesca Prignano; Gianni Gerlini; Benedetta Salvatori; Claudio Orlando; Sandra Mazzoli; Nicola Pimpinelli; Silvia Moretti (Clinical & Experimental Metastasis, 2006)

Clinical Epidemiology and Survival of Progressive Multifocal Leukoencephalopathy in the Era of Highly Active Antiretroviral Therapy: Data from the Italian Registry Investigative Neuro AIDS (IRINA) - Andrea Antinori; Antonella Cingolani; Patrizia Lorenzini; Maria Letizia Giancola; Ilaria Uccella; Simona Bossolasco; Susanna Grisetti; Francesca Moretti; Beniamino Vigo; Marco Bongiovanni; Bruno Del Grosso; Maria Irene Arcidiacono; et al. (Journal of NeuroVirology, 2003)

Light induced states in MbCO denatured with Guanidine hydrochloride - Francesca Natali; Lucia Moretti; Federico Boffi; Antonio Bianconi; Stefano Della Longa; A. Congiu Castellano (European Biophysics Journal, 1998)